2022
DOI: 10.4018/ijhcitp.293229
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Satisfaction and Intention to Stay Among Millennial Employees

Abstract: Purpose: The main purpose of the study is to investigate the relationship between job satisfaction, organizational commitment and intention to stay among the millennials working in IT organizations of North India. Research methodology: The present study has adopted descriptive research design and purposive sampling technique was used to gather data from 396 respondents with the help of a structured questionnaire. The data was analyzed using SPSS and PLS-SEM. Findings: Findings revealed that job satisfaction ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Likewise, self-concept, which describes an individual's mental representation and evaluation of competence [50], [63], is difficult to be actualized in driving a career without the support of leadership. Various literature states that the concepts of Career Motivation and Self Concept cannot be actualized to influence career insight, without managerial support [64]- [66]. Based on this explanation, the third and fourth hypotheses were formulated.…”
Section: Managerial Support As Moderatormentioning
confidence: 99%
“…Likewise, self-concept, which describes an individual's mental representation and evaluation of competence [50], [63], is difficult to be actualized in driving a career without the support of leadership. Various literature states that the concepts of Career Motivation and Self Concept cannot be actualized to influence career insight, without managerial support [64]- [66]. Based on this explanation, the third and fourth hypotheses were formulated.…”
Section: Managerial Support As Moderatormentioning
confidence: 99%
“…Thus, recent research (Thakur and Arora, 2022;Mane and Miravet, 2016;Marchiori et al, 2022; has shown that human capital makes a significant contribution to economic growth and technological development primarily through education, innovation and continuous growth. At the same time, the limited development of human capital leads to the use of natural resources as the main source of income, thereby reducing the level of the countries' economic development.…”
Section: Literature Reviewmentioning
confidence: 99%